National systems of innovation : toward a theory of innovation and interactive learning - Lundvall, Bengt-Åke, 1941- (London : Anthem Press, 2010)
℗'National Systems of Innovation℗' presents a new perspective on the dynamics of the national and the global economy.
Toward a new approach to national systems of innovation -- A closer look at national systems of innovation -- Opening national systems of innovation : specialisation, multinational corporations and integration.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Technological innovations -- Economic aspects; Technological innovations -- Government policy